PARÂMETROS UTILIZADOS NA MODIFICAÇÃO DA SUSPENSÃO DIANTEIRA DO BAJA - BONFADA, ANDERSON; KAFKA, DAVID; ABENTROTH, FERNANDO; GILAPA, GENARO M. M.; BARBIERI, JOAO R.; STAMM, JOÃO; CARPES, JONATAS V.; HEIMBURG, JULIO C. V.; DANETTE, LUCAS I.; BATAGLIN, MARCELO; et al. (Salão do Conhecimento, 2013)
Resumo